SAT0558 Shared Decision-Making in the Choice of Biologic Medication: the Patient Perspective. (23rd January 2014) - Bolge, S.; Eldridge, H.; Ingham, M.
Abstract : Background: There has been increasing focus on the importance of patients participating in the treatment decision-making process with their physicians. Previous research has demonstrated that effective physician-patient communication, a key component of shared decision-making, has a positive impact on patient satisfaction and adherence to therapy. 1 Objectives: To understand the patient role in decisions about mode of administration when initiating biologic therapy. Methods: In November 2011 through March 2012, semi-structured telephone interviews were conducted with 405 patients diagnosed with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS), currently using biologic therapy administered through subcutaneous injection (SQ), and residing in the United States. In August through September 2010, a similar study was conducted among a broader group of immunology patients currently using biologic therapy administered through intravenous infusion (IV), of which 209 were diagnosed with a rheumatology condition. The purpose of both studies was to better understand the patient experience with biologic therapies. Results: Among rheumatology patients currently using SQ biologic therapy, only 45.2% were offered an IV option prior to initiating SQ therapy. RA patients were more likely to be offered an IV option than PsA or AS patients [48.5% vs. 34.3% (p<0.10) and 37.1% (p<0.05), respectively]. Demographic characteristics including gender, age, race/ethnicity, household income, and education were not significantly associated with being offered an IV option. However, patients living in urban environments were more likely to be offered an IV option than patients living in rural environments (54.6% vs. 34.4%, p<0.05). So while less than half of current SQ users were offered an alternative, most SQ patients reported that they themselves made the decision to use a SQ therapy either independently (24.6%) or in partnership with their physician (56.8%). Only 15.3% of patients reported that their physician made the decision independently. Among rheumatology patients currently using IV biologic therapy, slightly more than half (54.1%) were also offered a SQ option prior to initiating IV therapy. As was the case with current SQ users, most current IV users reported that they themselves most greatly influenced the decision to use an IV therapy either independently (15.0%) or in partnership with their physician (44.2%), while 32.7% of patients reported that their physician most greatly influenced the decision. Conclusions: While many patients report being active decision makers, most often in partnership with their physician, patient decisions are quite frequently based on only a subset of the biologic therapy options available to them. For patients to be active participants in the shared-decision making process, they need to understand both SQ and IV options. Rheumatologist offices are well positioned to ensure that patients are provided the information and options needed to fully engage in the shared decision-making process for initiating biologic therapy. References: Elwyn G, et al. Shared decision-making in primary care: the neglected second half of the consultation. Br J Gen Pract 1999;49:477-82. Disclosure of Interest: S. Bolge Employee of: Janssen Scientific Affairs, LLC, H. Eldridge Employee of: Janssen Services, LLC, M. Ingham Employee of: Janssen Scientific Affairs, LLC